Positive electrode, nonaqueous electrolyte storage element, method for producing positive electrode, and method for producing nonaqueous electrolyte storage element
By using a high density positive electrode mixture in the positive electrode of the nonaqueous electrolyte power storage element, combining the positive electrode active substance of nickel and reducing organic acid, the resistance increase problem caused by high-density positive electrode mixture is solved, and resistance stability and energy are achieved Increased density.
Patent Information
- Application Number
- CN201880072412.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2017-11-08
- Filing Date
- 2018-11-06
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2038-11-06
AI Technical Summary
In the positive electrode of the nonaqueous electrolyte power storage element, high-density positive electrode mixture can easily lead to an increase in resistance during storage, especially when a positive electrode active substance containing nickel, the alkali component dissolution and substrate corrosion lead to an increase in resistance.
A positive electrode mixture with a density of 3.1 g/cm3 or more is used to contain a positive electrode active substance and a reducing organic acid. The phenomenon of increasing resistance is reduced by neutralizing the alkali component by reducing organic acid and inhibiting the oxidation of the substrate.
It effectively suppresses the increase in the resistance of the positive electrode, improves the energy density and stability of the non-aqueous electrolyte power storage element, and extends the service life of the equipment.
Smart Images

Figure CN111448688B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a positive electrode, a nonaqueous electrolyte energy storage element, a method for producing a positive electrode, and a method for producing a nonaqueous electrolyte energy storage element. Background Art
[0002] Non-aqueous electrolyte secondary batteries represented by lithium-ion secondary batteries are widely used in electronic devices such as personal computers, communication terminals, and automobiles because of their high energy density. The above-mentioned non-aqueous electrolyte secondary batteries generally have an electrode body having a pair of electrodes electrically isolated by a separator and a non-aqueous electrolyte sandwiched between the electrodes, and are configured in a manner of charging and discharging by the exchange of ions between the two electrodes. In addition, as non-aqueous electrolyte storage elements other than secondary batteries, capacitors such as lithium-ion capacitors and double-layer capacitors are also widely used.
[0003] The positive electrode of such a non-aqueous electrolyte storage element is widely used in which a positive electrode mixture layer containing a positive electrode active material is stacked on a conductive substrate. As the positive electrode active material, lithium transition metal composite oxides and the like are known, and there are also positive electrode active materials containing nickel such as lithium nickel composite oxides (see Patent Document 1).
[0004] Patent document 1: Japanese Patent Application Publication No. 2017-107827. Summary of the invention
[0005] The positive electrode is sometimes stored for a certain period after manufacture. On the other hand, in order to improve the energy density of the non-aqueous electrolyte storage element, it is preferred that the density of the positive electrode mixture is high. Among them, the inventors found that when the positive electrode active material contains nickel and the density of the positive electrode mixture is high, there is an undesirable phenomenon that the resistance of the positive electrode is easily increased with storage.
[0006] The present invention has been made based on the above circumstances, and its object is to provide a positive electrode and a method for producing the same, and a nonaqueous electrolyte storage element having the positive electrode and a method for producing the same, which can suppress resistance increase after storage even with a high-density positive electrode mixture.
[0007] A positive electrode according to one embodiment of the present invention made to solve the above-mentioned problems has a density of 3.1 g / cm 3 The above positive electrode mixture is a positive electrode for a non-aqueous electrolyte storage element containing a positive electrode active material containing nickel and a reducing organic acid.
[0008] A nonaqueous electrolyte energy storage device according to one embodiment of the present invention is a nonaqueous electrolyte energy storage device including the positive electrode.
[0009] A method for manufacturing a positive electrode according to one embodiment of the present invention is a method for manufacturing a positive electrode for a non-aqueous electrolyte storage element, comprising forming a positive electrode mixture paste having a density of 3.1 g / cm 3 In the above positive electrode mixture preparation step, the positive electrode mixture paste contains a positive electrode active material containing nickel and a reducing organic acid.
[0010] A method for producing a nonaqueous electrolyte energy storage device according to another aspect of the present invention is a method for producing a nonaqueous electrolyte energy storage device including the method for producing a positive electrode.
[0011] According to the present invention, a positive electrode and a method for producing the positive electrode can be provided that can suppress an increase in resistance after storage even if the positive electrode mixture has a high density, and a nonaqueous electrolyte storage device including the positive electrode and a method for producing the positive electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0012] Figure 1 It is a perspective view showing the appearance of a nonaqueous electrolyte secondary battery according to one embodiment of the present invention.
[0013] Figure 2 This is a schematic diagram showing a power storage device including a plurality of nonaqueous electrolyte secondary batteries according to an embodiment of the present invention. DETAILED DESCRIPTION
[0014] One embodiment of the present invention is a positive electrode for a non-aqueous electrolyte storage element having a density of 3.1 g / cm 3 The above positive electrode mixture contains a positive electrode active material containing nickel and a reducing organic acid.
[0015] Even if the positive electrode has a high-density positive electrode mixture, it can suppress the increase in resistance after storage. The reason is still uncertain, but it is speculated as follows. The positive electrode active material containing nickel has a lot of alkaline components. On the other hand, in general, metal foils such as aluminum are widely used as conductive substrates stacked with positive electrode mixtures in the positive electrode. In the case of storing such a previous positive electrode, the alkaline component sometimes dissolves into the water during storage, and the substrate corrodes (dissolves). The corrosion of the substrate leads to a decrease in the adhesion to the positive electrode mixture, etc., causing an increase in the resistance of the positive electrode. In particular, when the positive electrode mixture is high-density, the alkali concentration becomes high, so corrosion is easy to occur. In addition, it is speculated that the substrate reacts with oxygen in the atmosphere during storage to form an oxide film, and the insulation of the substrate surface becomes higher, which is also the reason for the increase in the resistance of the positive electrode. Compared with such a previous positive electrode, in the positive electrode of the present invention, the positive electrode mixture contains a reducing organic acid, so the alkaline component is neutralized, and the reducing organic acid is oxidized and can replace the oxidation (dissolution) of the substrate, so the corrosion of the substrate that is easily generated by the alkaline component is suppressed. It is also speculated that the oxidation of the substrate that improves the insulation properties can be suppressed by the reducing agent function of the reducing organic acid. It is speculated that the positive electrode of the present invention can suppress the increase in resistance after storage due to such function.
[0016] The density of the positive electrode mixture is the value obtained by dividing the mass of the positive electrode mixture by the apparent volume of the positive electrode mixture. The apparent volume is the volume including the voids, and when the positive electrode mixture is layered, it can be calculated as the product of the thickness and area of the positive electrode mixture.
[0017] The reducing organic acid is preferably a carboxylic acid. By using a carboxylic acid as the reducing organic acid, the effect of suppressing the increase in resistance after storage can be enhanced.
[0018] The carboxylic acid is preferably at least one selected from the group consisting of formic acid, oxalic acid, citric acid, malonic acid, lactic acid, tartaric acid, and gallic acid. By using such a carboxylic acid, the effect of suppressing the increase in resistance after storage is further increased.
[0019] Preferably, the content of nickel in the transition metal in the above-mentioned positive electrode active material is 33 mol% or more. In this way, when a positive electrode active material with a high nickel content is used, the alkali component in the positive electrode mixture becomes more, and there is a tendency to increase the resistance due to corrosion of the substrate. Therefore, when the content of nickel in the transition metal in the above-mentioned positive electrode active material is 33 mol% or more, the advantage of the present invention that the increase in resistance after storage is suppressed is more effectively obtained. In addition, "transition metal" refers to an element that exists between the 3rd group element and the 11th group element in the periodic table.
[0020] The content of the reducing organic acid is preferably 0.01 to 0.1 parts by mass based on 100 parts by mass of the positive electrode active material. When the content of the reducing organic acid is within the above range, an increase in resistance after storage is further suppressed.
[0021] One embodiment of the present invention is a nonaqueous electrolyte energy storage device (hereinafter, also simply referred to as an “energy storage device”) including the positive electrode. In the energy storage device, an increase in resistance of the positive electrode is suppressed.
[0022] One embodiment of the present invention is a method for producing a positive electrode for a non-aqueous electrolyte storage element, comprising: forming a positive electrode having a density of 3.1 g / cm 3 In the above positive electrode mixture preparation step, the positive electrode mixture paste contains a positive electrode active material containing nickel and a reducing organic acid. According to this production method, a positive electrode in which an increase in resistance after storage is suppressed can be obtained.
[0023] One embodiment of the present invention is a method for producing a nonaqueous electrolyte energy storage device including the method for producing a positive electrode. According to the production method, an energy storage device in which an increase in resistance of the positive electrode is suppressed can be obtained.
[0024] Hereinafter, as one embodiment of the present invention, a positive electrode, an electric storage element, and a method for manufacturing the same will be described in detail in sequence.
[0025] <Positive electrode>
[0026] A positive electrode according to one embodiment of the present invention includes a conductive substrate and a positive electrode mixture layer stacked on the substrate.
[0027] (Positive electrode substrate)
[0028] The positive electrode substrate has electrical conductivity. As the material of the substrate, metals such as aluminum, titanium, tantalum, stainless steel, or alloys thereof can be used. Among these, aluminum and aluminum alloys are preferred from the perspective of balancing potential resistance, high electrical conductivity, and cost. In addition, foil, vapor-deposited film, etc. can be cited as the formation form of the positive electrode substrate, and foil is preferred from the perspective of cost. That is, aluminum foil is preferred as the positive electrode substrate. In addition, as aluminum or aluminum alloy, A1085P, A3003P, etc. specified in JIS-H-4000 (2014) can be exemplified. In addition, in this specification, "electrical conductivity" means that the volume resistivity measured based on JIS-H-0505 (1975) is 10 7 Ω·cm or less.
[0029] (Positive electrode mixture layer)
[0030] The positive electrode mixture layer is a layer formed of a positive electrode mixture. The positive electrode mixture contains a positive electrode active material containing nickel and a reducing organic acid. The positive electrode mixture may contain any other components such as a conductive agent, a binder (adhesive), a thickener, and a filler as needed.
[0031] Examples of the positive electrode active material containing nickel include Li[Li x Ni 1-x ]O2(0≤x<0.5), Li[Li x Ni α Co (1-x-α) ]O2 (0≤x<0.5, 0<α<1), Li[Li x Ni α Mn β Co (1-x-α-β ]O2 (0≤x<0.5, 0<α, 0<β, 0.5<α+β<1) and other lithium transition metal composite oxides. In addition, polyanions such as LiNiPO4 can also be used. In the positive electrode mixture layer, one of these compounds can be used alone, or two or more can be mixed and used.
[0032] The lower limit of the content of nickel in the transition metal of the positive electrode active material containing nickel is preferably 33 mol %, more preferably 50 mol %. On the other hand, the upper limit of the content may be 100 mol % or 70 mol %.
[0033] The lower limit of the content of the positive electrode active material containing nickel in the positive electrode mixture layer is preferably 70% by mass, more preferably 80% by mass, and further preferably 85% by mass. On the other hand, the upper limit of the content of the positive electrode active material containing nickel is preferably 99% by mass, more preferably 95% by mass. By making the content of the positive electrode active material containing nickel within the above range, the capacity of the storage element can be increased.
[0034] The positive electrode mixture layer may further contain a positive electrode active material other than the positive electrode active material containing nickel. As such a positive electrode active material not containing nickel, a conventionally known positive electrode active material can be appropriately used.
[0035] The reducing organic acid is an organic acid having reducing properties. Reducing properties refer to the property of reducing other substances.
[0036] Examples of the reducing organic acid include carboxylic acids having reducing properties, ascorbic acid, isoascorbic acid, and the like, and carboxylic acids having reducing properties are preferred.
[0037] As carboxylic acid with reducing property, aliphatic carboxylic acids such as formic acid, oxalic acid, citric acid, malonic acid, lactic acid, tartaric acid, and aromatic carboxylic acids such as gallic acid can be cited. Among these, aliphatic carboxylic acids are preferably used, formic acid, oxalic acid and citric acid are more preferably used, and citric acid is further preferably used. These reducing organic acids have both appropriate acidity and reducing property, and can further give full play to the resistance increase after suppressing storage. In addition, hydroxycarboxylic acids (carboxylic acids with hydroxyl groups) such as citric acid and lactic acid are also preferably used. Reducing organic acids can use one or more than two kinds.
[0038] As the lower limit of the content of the above-mentioned reducing organic acid, it is preferably 0.01 parts by mass relative to 100 parts by mass of the positive electrode active material containing the above-mentioned nickel, more preferably 0.02 parts by mass, further preferably 0.03 parts by mass, further preferably 0.04 parts by mass, and further preferably 0.05 parts by mass. By making the content of the reducing organic acid above the above lower limit, the increase in resistance can be further suppressed. On the other hand, as the upper limit of the content, it is preferably 0.1 parts by mass, more preferably 0.08 parts by mass. When the content of the reducing organic acid exceeds the above upper limit, the effect tends to reach the top, therefore, by making the content below the above upper limit, production costs can be suppressed.
[0039] The conductive agent is not particularly limited as long as it is a conductive material that does not negatively affect the performance of the storage element. Examples of such conductive agents include natural or artificial graphite, furnace black, acetylene black, ketjen black and other carbon blacks, metals, conductive ceramics, etc. Examples of the conductive agent include powdery and fibrous shapes.
[0040] Examples of the above-mentioned adhesives (binders) include thermoplastic resins such as fluororesins (polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, etc.), polyethylene, polypropylene, polyimide, etc.; elastomers such as ethylene-propylene-diene rubber (EPDM), sulfonated EPDM, styrene-butadiene rubber (SBR), fluororubber, etc.; polysaccharide polymers, etc.
[0041] As the above-mentioned adhesive, it is sometimes preferred that it does not have rubber elasticity in fact. In addition, the adhesive with rubber elasticity usually has a three-dimensional mesh structure and has elasticity above the glass transition temperature. In addition, as the above-mentioned adhesive, it is sometimes preferred that the material other than N-methoxymethylated nylon. Among the above-mentioned adhesives, it is preferably a fluororesin, more preferably PVDF.
[0042] Examples of the thickener include polysaccharide polymers such as carboxymethyl cellulose (CMC) and methyl cellulose. When the thickener has a functional group that reacts with lithium, it is preferred that the functional group be inactivated in advance by methylation or the like.
[0043] The filler is not particularly limited as long as it does not have a negative impact on the performance of the storage device. Examples of the main component of the filler include polyolefins such as polypropylene and polyethylene, silica, alumina, zeolite, and glass.
[0044] The average thickness of the positive electrode mixture layer is not particularly limited, and may be, for example, 30 μm to 200 μm.
[0045] The lower limit of the density of the positive electrode mixture layer (positive electrode mixture) is 3.1 g / cm 3 In this positive electrode, the resistance increase after storage, which is usually easy to occur when the density of such a positive electrode mixture layer is high, can be suppressed. In addition, the high density of such a positive electrode mixture layer can increase the energy density of the storage element. In addition, as the upper limit of this density, 4 g / cm 3 , more preferably 3.4 g / cm 3 The density of the positive electrode mixture layer can be adjusted by the particle size and particle size distribution of the positive electrode active material and other components, the pressing in the manufacturing process, etc. For example, by mixing and using a plurality of positive electrode active materials with different particle sizes, the density of the formed positive electrode mixture layer can be increased.
[0046] <Non-aqueous electrolyte storage element>
[0047] The storage element involved in one embodiment of the present invention has a positive electrode, a negative electrode and a non-aqueous electrolyte. Below, as an example of a storage element, a secondary battery is described. The positive electrode and the negative electrode are usually formed as an electrode body stacked or wound with a separator. The electrode body is accommodated in a shell, and the shell is filled with the non-aqueous electrolyte. The non-aqueous electrolyte is sandwiched between the positive electrode and the negative electrode. In addition, as the shell, a known metal shell, a resin shell, etc. commonly used as a shell of a secondary battery can be used.
[0048] (positive electrode)
[0049] The positive electrode included in this secondary battery is the positive electrode according to the above-mentioned embodiment of the present invention.
[0050] (negative electrode)
[0051] The negative electrode comprises a negative electrode substrate and a negative electrode mixture layer disposed on the negative electrode substrate directly or via an intermediate layer.
[0052] As the material of the negative electrode substrate, metals such as copper, nickel, stainless steel, nickel-plated steel, or alloys thereof can be used, preferably copper or copper alloys. That is, copper foil is preferably used as the negative electrode substrate. Examples of copper foil include rolled copper foil, electrolytic copper foil, and the like.
[0053] The negative electrode mixture layer is formed of a so-called negative electrode mixture containing a negative electrode active material. In addition, the negative electrode mixture forming the negative electrode mixture layer contains any components such as a conductive agent, a binder (adhesive), a thickener, and a filler as required. The conductive agent, binder, thickener, filler, and other arbitrary components can use the same substances as those of the positive electrode mixture layer.
[0054] As the above-mentioned negative electrode active material, a material capable of embedding and de-embedding lithium ions can generally be used. As specific negative electrode active materials, for example, metals or semimetals such as Si and Sn; metal oxides or semimetal oxides such as Si oxide and Sn oxide; polyphosphorus oxides; carbon materials such as graphite and non-graphite carbon (graphitizable carbon or non-graphitizable carbon) can be cited.
[0055] In addition, the negative electrode mixture layer may contain typical non-metallic elements such as B, N, P, F, Cl, Br, I, typical metal elements such as Li, Na, Mg, Al, K, Ca, Zn, Ga, Ge, and transition metal elements such as Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Mo, Zr, Ta, Hf, Nb, and W.
[0056] (Isolator)
[0057] The separator isolates the positive electrode from the negative electrode and plays a role in maintaining the non-aqueous electrolyte. As the material of the separator, for example, woven fabrics, non-woven fabrics, porous resin films, etc. can be used. Among these, porous resin films are preferably used. As the main component of the porous resin film, polyolefins such as polyethylene and polypropylene are preferably used from the viewpoint of strength. In addition, porous resin films obtained by compounding these resins with resins such as aromatic polyamides and polyimides can be used.
[0058] (Non-aqueous electrolyte)
[0059] The non-aqueous electrolyte contains a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. The non-aqueous electrolyte may contain other additives.
[0060] As the above-mentioned non-aqueous solvent, a known non-aqueous solvent commonly used as a non-aqueous solvent for a non-aqueous electrolyte for a general storage element can be used. As the above-mentioned non-aqueous solvent, cyclic carbonates, chain carbonates, esters, ethers, amides, sulfones, lactones, nitriles, etc. can be cited. Among these, it is preferred to use at least cyclic carbonates or chain carbonates, and it is more preferred to use cyclic carbonates and chain carbonates in combination. When a cyclic carbonate and a chain carbonate are used in combination, the volume ratio of the cyclic carbonate to the chain carbonate (cyclic carbonate: chain carbonate) is not particularly limited, and is preferably, for example, 5:95 to 50:50.
[0061] Examples of the cyclic carbonate include ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinylene carbonate (VC), vinyl ethylene carbonate (VEC), vinyl chloride carbonate, fluoroethylene carbonate (FEC), difluoroethylene carbonate (DFEC), styrene carbonate, catechol carbonate, 1-phenylethylene carbonate, and 1,2-diphenylethylene carbonate.
[0062] Examples of the linear carbonate include diethyl carbonate (DEC), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), and diphenyl carbonate.
[0063] As the electrolyte salt, a known electrolyte salt commonly used as an electrolyte salt of a general non-aqueous electrolyte for a storage element can be used. Examples of the electrolyte salt include lithium salts, sodium salts, potassium salts, magnesium salts, Salts, etc., preferably lithium salts.
[0064] As the above-mentioned lithium salts, there can be mentioned inorganic lithium salts such as LiPF6, LiPO2F2, LiBF4, LiClO4, LiN(SO2F)2, and lithium salts having fluorinated hydrocarbon groups such as LiSO3CF3, LiN(SO2CF3)2, LiN(SO2C2F5)2, LiN(SO2CF3)(SO2C4F9), LiC(SO2CF3)3, and LiC(SO2C2F5)3.
[0065] As the non-aqueous electrolyte, room-temperature molten salt, ionic liquid, polymer solid electrolyte, or the like may be used.
[0066] <Method for manufacturing positive electrode>
[0067] A method for manufacturing a positive electrode according to an embodiment of the present invention includes forming a positive electrode mixture paste having a density of 3.1 g / cm 3 In the method for producing a positive electrode for a non-aqueous electrolyte storage device in the above positive electrode mixture process, the positive electrode mixture paste contains a positive electrode active material containing nickel and a reducing organic acid.
[0068] By mixing the positive electrode active material containing the above-mentioned nickel and the reducing organic acid, a positive electrode mixture paste is obtained. In addition, the preferred range of the amount of reduction organic acid added (mixed amount) relative to the positive electrode active material containing nickel is the same as the preferred range of the content of the reduction organic acid relative to the positive electrode active material containing nickel in the above-mentioned positive electrode mixture layer (positive electrode mixture). The positive electrode is obtained by applying the positive electrode mixture paste directly or through an intermediate layer on the surface of the positive electrode substrate and drying it. In addition to these, the positive electrode mixture paste may also contain any components that can be included in the above-mentioned positive electrode mixture.
[0069] In the positive electrode mixture paste, an organic solvent is usually used as a dispersion medium. Examples of the organic solvent include polar solvents such as N-methyl-2-pyrrolidone (NMP), acetone, and ethanol, and non-polar solvents such as xylene, toluene, and cyclohexane.
[0070] The coating method of the positive electrode mixture paste is not particularly limited, and can be performed by known methods such as roller coating, screen coating, and spin coating. In addition, after coating or drying, the positive electrode mixture layer can be squeezed in the thickness direction by a known method. In this way, by pressing the positive electrode mixture layer, the density of the positive electrode mixture layer can be increased.
[0071] <Method for Manufacturing Non-Aqueous Electrolyte Storage Element>
[0072] A method for producing a nonaqueous electrolyte electricity storage device according to one embodiment of the present invention is a method for producing a nonaqueous electrolyte electricity storage device including the above-mentioned method for producing a positive electrode.
[0073] In this manufacturing method, in addition to obtaining the positive electrode by the above-mentioned manufacturing method, a previous manufacturing method can be adopted. This manufacturing method, for example, has a process for making the above-mentioned positive electrode, in addition, has a process for making a negative electrode, a process for preparing a non-aqueous electrolyte, a process for forming an electrode body alternately overlapped by stacking or winding the positive electrode and the negative electrode across a separator, a process for accommodating the positive electrode and the negative electrode (electrode body) in a battery container, and a process for injecting the above-mentioned non-aqueous electrolyte into the above-mentioned battery container. By sealing the injection port after injection, a non-aqueous electrolyte secondary battery (non-aqueous electrolyte storage element) can be obtained. The details of each element constituting the non-aqueous electrolyte storage element (secondary battery) obtained by the manufacturing method are as described above.
[0074] <Other Embodiments>
[0075] The present invention is not limited to the above-mentioned embodiments, and can be implemented in various ways with various changes and improvements other than the above-mentioned embodiments. For example, no intermediate layer may be provided in the above-mentioned positive electrode or negative electrode. In addition, in the positive electrode, the positive electrode mixture may not form a clear layer. For example, the above-mentioned positive electrode may be a structure in which the positive electrode mixture is supported on a mesh-shaped positive electrode substrate.
[0076] In addition, in the above embodiment, the non-aqueous electrolyte storage element is described as a non-aqueous electrolyte secondary battery, but it can also be other non-aqueous electrolyte storage elements. As other non-aqueous electrolyte storage elements, capacitors (electric double layer capacitors, lithium ion capacitors) and the like can be cited.
[0077] Figure 12 is a schematic diagram of a rectangular nonaqueous electrolyte secondary battery 1 (secondary battery 1) according to one embodiment of the nonaqueous electrolyte storage element of the present invention. The figure is a perspective view of the inside of a container. Figure 1 In the secondary battery 1 shown, the electrode body 2 is accommodated in the battery container 3. The electrode body 2 is formed by winding a positive electrode having a positive electrode active material and a negative electrode having a negative electrode active material through a separator. The positive electrode is electrically connected to the positive terminal 4 via a positive electrode lead 4', and the negative electrode is electrically connected to the negative terminal 5 via a negative electrode lead 5'. In addition, a non-aqueous electrolyte is injected into the battery container 3. In addition, the specific structure of each element such as the positive electrode is as described above.
[0078] The structure of the non-aqueous electrolyte storage element involved in the present invention is not particularly limited, and as an example, a cylindrical battery, a rectangular battery (rectangular battery), a flat battery, etc. can be cited. The present invention can also be implemented as a storage device having a plurality of the above-mentioned non-aqueous electrolyte storage elements. One embodiment of the storage device is shown in Figure 2 . Figure 2 In the embodiment, the power storage device 30 includes a plurality of power storage units 20. Each power storage unit 20 includes a plurality of secondary batteries 1. The power storage device 30 can be mounted as a power source for vehicles such as electric vehicles (EV), hybrid electric vehicles (HEV), and plug-in hybrid electric vehicles (PHEV).
[0079] Example
[0080] Hereinafter, the present invention will be described in further detail based on examples, but the present invention is not limited to the following examples.
[0081] [Example 1]
[0082] (positive electrode)
[0083] LiNi is used as the positive electrode active material 1 / 3 Mn 1 / 3 Co 1 / 3 A positive electrode mixture paste was prepared by using O2, citric acid as a reducing organic acid, acetylene black (AB) as a conductive agent, polyvinylidene fluoride (PVDF) as a binder, and N-methylpyrrolidone (NMP) as a dispersion medium. The mass ratio of the positive electrode active material, the binder, and the conductive agent is 90.5:4.5:5.0 (solid content conversion). In addition, the content of citric acid is 0.04 parts by mass relative to 100 parts by mass of the positive electrode active material. The positive electrode mixture paste is intermittently applied to both sides of an aluminum foil (thickness 16 μm) serving as a positive electrode substrate in a manner that leaves a non-forming portion of the positive electrode mixture layer, and the positive electrode mixture layer is formed by drying it. Thereafter, the surface of the positive electrode mixture layer is rolled to obtain a positive electrode. The thickness of the obtained positive electrode is 140 μm, and the density of the positive electrode mixture (positive electrode mixture layer) is 3.1 g / cm3 .
[0084] [Examples 2 to 5, Comparative Examples 1 to 6]
[0085] The type and content of the organic acid (reducing organic acid or other organic acid) and the density of the positive electrode mixture are shown in Tables 1 and 2. Except for this, the positive electrodes of Examples 2 to 5 and Comparative Examples 1 to 6 were obtained in the same manner as in Example 1. In addition, the pressing pressure on the surface of the positive electrode mixture layer was appropriately changed to adjust the density of the positive electrode mixture. In addition, maleic acid in Table 2 is an organic acid that does not have reducing properties.
[0086] [evaluate]
[0087] (Surface resistance measurement before storage)
[0088] For each positive electrode prepared as described above, the resistance of the mixture layer surface was measured using a surface resistance meter ("Loresta FP" manufactured by Mitsubishi Chemical Corporation, MCP-TESTER using a 4-probe probe) in an environment of 25°C and a dew point of 0°C or less.
[0089] (Surface resistance measurement after storage 1)
[0090] Each positive electrode of Examples 1 to 2 and Comparative Examples 1 to 4, for which the surface resistance before storage was measured, was stored for two weeks at a temperature of 30°C and a relative humidity of 55%. For each positive electrode after storage, the surface resistance was measured using the same method as in the above "Measurement of surface resistance before storage". The percentage of the surface resistance value after storage relative to the surface resistance value before storage is shown in Table 1 as the surface resistance increase rate (%).
[0091] (Surface resistance measurement after storage 2: accelerated test)
[0092] The positive electrodes of Examples 3 to 5 and Comparative Examples 5 to 6, for which the surface resistance before storage was measured, were stored for two weeks at a temperature of 50°C and a relative humidity of 75%. The surface resistance of each positive electrode after storage was measured using the same method as in the above "Measurement of surface resistance before storage". The percentage of the surface resistance value after storage relative to the surface resistance value before storage is shown in Table 2 as the surface resistance increase rate (%).
[0093] [Table 1]
[0094]
[0095] [Table 2]
[0096]
[0097] The results in Table 1 show the following: When comparing Comparative Examples 1 to 3, the density of the positive electrode mixture is 3.1 g / cm 3 In the above cases (Comparative Examples 2 and 3), the surface resistance after storage increased significantly. In contrast, as shown in Examples 1 and 2, it is found that the surface resistance of the 3 The positive electrode mixture contains citric acid as a reducing organic acid, which can suppress the increase of surface resistance. On the other hand, from the comparison between Comparative Example 1 and Comparative Example 4, it can be seen that when the density of the positive electrode mixture is less than 3.1 g / cm 3 In the case of 3.1 g / cm density, even if citric acid is contained in the positive electrode mixture, the effect of suppressing the increase in surface resistance is not produced. That is, the effect of suppressing the increase in resistance of the positive electrode after storage is only about 3.1 g / cm density. 3 The above positive electrode mixture will only produce an effect when it contains a reducing organic acid.
[0098] In addition, as shown in Table 2, when Examples 3 to 5 are compared, it can be seen that the effect of suppressing the increase in surface resistance becomes higher by increasing the content of citric acid as a reducing organic acid. On the other hand, in Comparative Example 7 using maleic acid as an organic acid that does not have reducing properties, there is almost no effect of suppressing the increase in surface resistance. From such results, it can be seen that the effect of suppressing the increase in resistance of the positive electrode after storage is an effect that can only be produced by using an additive having both acidity and reducing properties.
[0099] Industrial Applicability
[0100] The present invention can be applied to nonaqueous electrolyte storage elements represented by nonaqueous electrolyte secondary batteries used as power sources for electronic devices such as personal computers and communication terminals, and automobiles.
[0101] Description of Reference Numerals
[0102] 1 Non-aqueous electrolyte secondary battery
[0103] 2 Electrode body
[0104] 3 Battery container
[0105] 4 Positive terminal
[0106] 4' positive lead
[0107] 5 Negative terminal
[0108] 5' negative lead
[0109] 20 Storage unit
[0110] 30 Power storage device
Claims
1. A positive electrode for a non-aqueous electrolyte storage element, comprising: a positive electrode substrate containing aluminum or an aluminum alloy and a layer having a density of 3.1 g / cm2 stacked on the positive electrode substrate 3 ~4g / cm 3 The positive electrode mixture, The positive electrode mixture contains a positive electrode active material containing nickel and a reducing organic acid, wherein the positive electrode active material has a layered α-NaFeO2 type crystal structure. The reducing organic acid is a hydroxycarboxylic acid.
2. The positive electrode according to claim 1, wherein The hydroxycarboxylic acid is at least one selected from the group consisting of citric acid, lactic acid, tartaric acid and gallic acid.
3. The positive electrode according to claim 1 or 2, wherein Among the transition metals in the positive electrode active material, the content of nickel is 33 mol % or more.
4. The positive electrode according to claim 1 or 2, wherein The content of the reducing organic acid is 0.01 to 0.1 parts by mass relative to 100 parts by mass of the positive electrode active material.
5. The positive electrode according to claim 3, wherein The content of the reducing organic acid is 0.01 to 0.1 parts by mass relative to 100 parts by mass of the positive electrode active material. 6 . A non-aqueous electrolyte storage element comprising the positive electrode according to claim 1 .
7. A method for manufacturing a positive electrode for a non-aqueous electrolyte storage element, comprising forming a positive electrode having a density of 3.1 g / cm 3 ~4g / cm 3 The process of preparing the positive electrode mixture, The positive electrode mixture paste contains a positive electrode active material containing nickel and a reducing organic acid, wherein the positive electrode active material has a layered α-NaFeO2 type crystal structure. The reducing organic acid is a hydroxycarboxylic acid.
8. A method for producing a non-aqueous electrolyte storage element, comprising the method for producing a positive electrode according to claim 7.
Citation Information
Patent Citations
Positive electrode active material for nonaqueous electrolyte secondary battery, and method for producing the same, and nonaqueous electrolyte secondary battery
JP2017107827A
Positive electrode mixture for nonaqueous battery and positive electrode structure
CN101855752A
Non-aqueous secondary battery
CN103891028A